The effect of additional protein intake via dietary education combined with recording on physical performance in sarcopenic elderly: A randomized controlled trial - Thongwilas, Sasiwimol (Journal of Nakornping Hospital, 2024)
Objective : This study aims to investigate the improvement of nutritional knowledge and physical performance in sarcopenic elderly individuals through increased protein intake facilitated by dietary counseling and record-keeping, comparing a group receiving only nutritional education with a group that additionally keeps dietary records. Methodology: This was a randomized controlled trial conducted in San Sai Hospital from October to November 2022, involving 152 participants divided into two groups of 76 each. One group received nutritional education while the other group also kept food diary records. The study followed participants for a period of 10 months, with data collected at 4 and 6 months. Outcomes included the 4-Meter Gait Speed Test, Timed Up and Go test, Short Physical Performance Battery (SPPB), Mini Nutritional Assessment (MNA), Morse Fall Scale, Thai Mini-Mental State Examination (TMSE), and WHO Quality of Life (WHOQOL) questionnaire. Results : A total of 152 participants were included in the study, with 60.5% being female and an average age of 64.90 ± 3.42 years. The average BMI was 22.54 ± 1.88 kg/m². Both groups showed no statistical difference at baseline. Outcomes measured at 4 weeks, 8 weeks, 12 weeks, and 6 months showed significant improvements from 4 weeks of follow-up in all measured aspects in the experimental group compared to the control group. At 4 weeks, the results in the experimental group compared to the control group were as follows: 4-Meter Gait Speed Test: 2.77 ± 0.06 vs. 2.86 ± 0.05 seconds (p < 0.001),Timed Up and Go Test: 12.77 ± 0.06 vs. 14.39 ± 0.30 seconds (p < 0.001),Short Physical Performance Battery (SPPB): 7.00 ± 0.00 vs. 6.00 ± 0.00 points (p < 0.001),Mini Nutritional Assessment (MNA): 9.61 ± 2.89 vs. 9.08 ± 0.73 points (p < 0.001),Morse Fall Scale: 75.00 ± 0.00 vs. 90.00 ± 0.00 points (p < 0.001),Thai Mini-Mental State Examination (TMSE): 25.55 ± 0.60 vs. 24.77 ± 0.59 points (p < 0.001), and WHO Quality of Life (WHOQOL): 80.00 ± 0.00 vs. 76.00 ± 0.00 points (p < 0.001). These results indicate significant improvements in the experimental group compared to the control group. Conclusion : Providing education on additional protein intake via dietary counseling, combined with meticulous recording, enables sarcopenic elderly individuals at San Sai Hospital in Chiang Mai Province to significantly improve physical performance and retain nutritional knowledge. This approach proves to be statistically more effective compared to providing education alone.